The last Ottoman generation and the making of the modern Middle East - Provence, Michael, 1966- (Cambridge, United Kingdom : Cambridge University Press, 2017)
The modern Middle East emerged out of the collapse of the Ottoman Empire, when Britain and France partitioned the Ottoman Arab lands into several new colonial states. The following period was a charged and transformative time of unrest. Insurgent leaders, trained in Ottoman military tactics and with everything to lose from the fall of the Empire, challenged the mandatory powers in a number of armed revolts. This is a study of this crucial period in Middle Eastern history, tracing the period through popular political movements and the experience of colonial rule. In doing so, Provence emphasises the continuity between the late Ottoman and Colonial era, explaining how national identities emerged, and how the seeds were sown for many of the conflicts which have defined the Middle East in the late twentieth and early twenty-first centuries. This is a valuable read for students of Middle Eastern history and politics.
Introduction -- Saladin's pilgrims and the war to end war -- Modernity, militarism, and colonialism in the making of the Middle East -- Ottoman modernity -- Middle East colonialisms -- Legacies -- 1) Ottoman modernity in the long nineteenth century : training state servants and making citizens -- Modern education and a late Ottoman childhood -- Modernizing the state -- Conscription -- State military education and elite civil education -- Military culture and late Ottoman society -- The military academy and staff college -- Modern infrastructure -- Ottoman sons become saviors of the nation -- Civilian politicians and civil school graduates -- Conclusions -- 2) The theory and practice of colonialism in the post-Ottoman Middle East -- Wartime arrangements and proclamations -- The Paris Peace Conference and post-war negotiations -- The San Remo Conference and the Treaty of Sèvres -- The League of Nations and Anglo-French colonialism in the Middle East -- Mandate governance in practice -- The mandate in Palestine -- The mandate in Syria and Lebanon -- The mandate in Iraq and Transjordan -- Conclusions -- 3) Losing the war and fighting the settlement : the post-Ottoman Middle East takes shape, 1918-1922 -- The Battle of Nablus and the end of the Ottoman Empire -- Allenby and Faysal in Damascus -- Popular struggle after the armistice -- The Anatolian model and hope for salvation, 1920 -- San Remo and the Nabi Musa demonstrations in Jerusalem -- Iraq in revolt -- Anatolia and Cilicia -- Syria and Maysalun -- Churchill salvages the settlement -- Palestine May Day riots 1921 -- Ibrahim Hananu puts the settlement on trial -- Events in Anatolia -- Yasin paa returns to Iraq -- The last sultan -- Conclusions -- 4) League of Nations hopes and disappointments : the return of armed struggle in the post-Ottoman era, 1923-1927 -- The Lausanne Conference -- The League of Nations picks up the pieces -- The end of the caliphate -- Military confrontation eclipsed -- Civilian politicians in Damascus and Jerusalem -- Shakib Arslan in exile -- The rise of Yasin al-Hashimi and the Anglo-Iraqi treaty -- Armed insurgency in the French mandates -- France salvages its mandate -- William Rappard, the League of Nations, and France -- The end of the Syrian revolt -- Damage control at Geneva -- Aftermath of the Syrian revolt -- Colonial anxieties and imperial rivalries -- Conclusions -- 5) Colonial constitutions and treaties : post-Ottoman militarism, 1927-1936 -- Constitutions and colonial treaties : Iraq -- Syrian and Lebanon -- Transjordan -- Palestine : 1928 and 1929 -- Nuri al-Sacid delivers : the Anglo-Iraqi treaty of 1930 -- Syrian elections and martial law -- Independent Iraq -- Iraqi independence and its discontents -- Ibrahim Hananu and a false start for the Franco-Syrian treaty -- Desperation in Palestine and the death of Musa Kazim -- Yasin al-Hashimi retires and then returns -- Fawzi al-Qawuqji in Baghdad -- Ibrahim Hananu exits the scene -- Conclusions -- 6) The final days of the last Ottoman generation, 1936-1938 -- General strikes in Syria and Palestine -- The Palestine revolt -- The Franco-Syrian treaty and Syrian "independence" -- The fall of Yasin al-Hashimi -- Yasin paa in exile among the Syrians -- The death and funeral of Yasin al-Hashimi -- Conclusions -- 7) Epilogue and conclusion -- Saladin's companions and the beginning of the end for Anglo-French colonialism in the Middle East -- The Alexandretta crisis -- The Peel commission and the end of the Palestine mandate -- General amnesty in Syria -- The end of the League of Nations mandates -- The mandate inheritance in the Arab East.
Includes bibliographical references and index.
Keywords: Middle East -- History -- 20th century; Turkey -- History -- 20th century